Some Short Thoughts on Morality, Ecology and Nature - Miller, Laurie (UnderCurrents: Journal of Critical Environmental Studies, 1996)
Nature Knows Best, and as Neil Evernden has pointed out perhaps facetiously, Ecology Knows Nature (1992: 8). However, for a number of reasons, these statements have become truisms for many of those who environmentalists — seems to reveal the moral order of being by simultaneously uncovering the verum, bonum and pulchrum of reality: it suggests not only the truth, but also a moral imperative and even aesthetic perfection" (Sachs, 1992: 32). [...]